Regulation of Monospecies and Mixed Biofilms Formation of Skin Staphylococcus aureus and Cutibacterium acnes by Human Natriuretic Peptides - Gannesen, Andrei Vladislavovich; Lesouhaitier, Olivier; Racine, Pierre-Jean; Barreau, Magalie; Netrusov, Alexander I.; Plakunov, Vladimir K.; Feuilloley, Marc G. J. (Frontiers in Microbiology, 2018)
Staphylococcus aureus and Cutibacterium acnes are common representatives of human skin microbiome. However, these bacteria organized in biofilm could be involved in a number of skin disorders such as acne or psoriasis. They inhabit hollows of hair follicles and skin glands in which they form biofilms. Here, there are continuously exposed to human hormones including the human natriuretic peptides (NUPs). We first observed that the atrial natriuretic peptide (ANP) and the C-type natriuretic peptide (CNP) have a strong effect on the skin S. aureus and C. acnes biofilm formation. These effects are significantly dependent of the aero-anaerobic conditions and of the temperature. We also showed that both ANP and CNP increased competitive advantages of C. acnes towards S. aureus in mixed biofilm. Because of their temperature dependent effects, NUPs appear to act as thermostat allowing the skin to modulate bacterial development in normal and inflammatory conditions. This is an important step to understanding of how human neuroendocrine systems can regulate the cutaneous microbial community and should be important for application in fundamental sciences, medicine, dermatology and cosmetology.